2000
DOI: 10.1002/(sici)1099-0720(200001)14:1<31::aid-acp622>3.0.co;2-9
|View full text |Cite
|
Sign up to set email alerts
|

Forgetting near-accidents: the roles of severity, culpability and experience in the poor recall of dangerous driving situations

Abstract: It is often assumed that real‐life events such as minor road accidents and near accidents will be well remembered. However, surveys of self‐reported accidents suggest that respondents apparently forget approximately one third of their road accidents each year. This paper explores this possibility by looking at memory for the near‐accidents in which drivers are involved. In a pilot study drivers carried microcassette recorders in their cars and reported near‐accidents after each journey. These data confirmed th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
35
0
1

Year Published

2002
2002
2021
2021

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 82 publications
(36 citation statements)
references
References 34 publications
0
35
0
1
Order By: Relevance
“…The accuracy of self-reported near-crashes, which are much more common, is even more doubtful than that of self-reported crashes. Chapman and Underwood [6] found that 80 % of near-crashes were forgotten after two weeks.…”
Section: Self-reports (Sr)mentioning
confidence: 99%
“…The accuracy of self-reported near-crashes, which are much more common, is even more doubtful than that of self-reported crashes. Chapman and Underwood [6] found that 80 % of near-crashes were forgotten after two weeks.…”
Section: Self-reports (Sr)mentioning
confidence: 99%
“…In assessment of on-road accident liability, such events would be called near-accidents, and defined as incidents where the driver retrospectively considered there to be a possibility of an accident causing damage or injury. In a recent study on memory for near-accidents, Chapman and Underwood (2000) found that 43 participants reported 382 near-accidents across 3592 journeys (recorded on dictaphones after each journey). On this basis the number of experiences similar to the type of events portrayed in the clips will be considerably higher for any individual than the actual number of accidents they have had, and therefore the rise in exposure to such events with increasing driving experience should be more marked.…”
Section: Peripheral Target Detectionmentioning
confidence: 99%
“…For instance, there are plentiful cases of convictions arising from mistaken eyewitness identification (e.g. Pezdek, 2012), indicating a failure of memory, and events such as nearaccidents on the road appear to be forgotten with alarming speed (Chapman & Underwood, 2000). Understanding the processes surrounding memory distortion is therefore extremely important and, unsurprisingly, there is a long history of research examining forgetting within experimental psychology (e.g.…”
Section: Introductionmentioning
confidence: 99%